2013
DOI: 10.1021/ja411017b
|View full text |Cite
|
Sign up to set email alerts
|

Hot-Electron-Induced Dissociation of H2on Gold Nanoparticles Supported on SiO2

Abstract: Hot-electron-induced photodissociation of H2 was demonstrated on small Au nanoparticles (AuNPs) supported on SiO2. The rate of dissociation of H2 was found to be almost 2 orders of magnitude higher than that observed on equivalently prepared AuNPs on TiO2. The rate of H2 dissociation was found to be linearly dependent on illumination intensity with a wavelength dependence resembling the absorption spectrum of the plasmon of the AuNPs. This result provides strong additional support for the hot-electron-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
500
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 481 publications
(517 citation statements)
references
References 31 publications
9
500
1
Order By: Relevance
“…S7 and Table S2) because of the very exothermic and barrier-free dissociative adsorption of H 2 on Pd(111), consistent with recent literature (32,33). Thus, we believe that the more consequential process for Pd-in contrast to earlier reports of plasmon-induced dissociation of H 2 on Au (7,8) and Al (15)-is the interaction of the generated hot carriers with adsorbed H and D atoms on Pd, inducing desorption of HD. The plasmon-induced dissociation, recombination, and desorption processes are all charge-neutral.…”
Section: Resultssupporting
confidence: 88%
“…S7 and Table S2) because of the very exothermic and barrier-free dissociative adsorption of H 2 on Pd(111), consistent with recent literature (32,33). Thus, we believe that the more consequential process for Pd-in contrast to earlier reports of plasmon-induced dissociation of H 2 on Au (7,8) and Al (15)-is the interaction of the generated hot carriers with adsorbed H and D atoms on Pd, inducing desorption of HD. The plasmon-induced dissociation, recombination, and desorption processes are all charge-neutral.…”
Section: Resultssupporting
confidence: 88%
“…3 While the design of heterogeneous photocatalysts has focused largely on semiconducting light absorbers, 4,5 it has recently been demonstrated that metallic nanostructures offer unique characteristics for facilitating photocatalytic reactions. [6][7][8][9] Strong light absorption through the excitation of localized surface plasmons on plasmonic metal nanostructures 10 comprised of Au, [11][12][13] Ag, [14][15][16] Cu, 17 or Al, 18 has been shown to drive photocatalytic processes through the excitation and transient transfer of energetic, or hot, carriers to adsorbates. [19][20][21][22][23][24] However, there is limited evidence that the energies of hot carriers in plasmonic nanostructures can be selectively tailored to target specific catalytic reaction pathways, 25,26 and plasmonic nanostructures are optimal catalysts for only a very few 4 relevant industrial chemical processes.…”
Section: Main Textmentioning
confidence: 99%
“…Chen et al showed that Au NPs are active for HCHO oxidation to CO 2 under 600-700 nm red light irradiation [13,33,127,128]. Hot electrons can drive also H 2 dissociation on plasmonic Au NPs at room temperature and laser intensity of~2 W cm −2 [129,130]. Plasmonic nanostructures have also been reported to drive the selective oxidation of secphenethyl alcohol to acetophenone under LSPR excitation of aqueous colloidal Au NPs with visible light [131].…”
Section: Direct Plasmonic Photocatalysismentioning
confidence: 99%